Grounded source transient electromagnetic 3D forward modeling with the spectral-element method and its application in hydraulic fracturing monitoring - Huang, Xin; Yan, Liangjun; Wang, Xingyu; Xie, Xingbing; Zhou, Lei; Cao, Xiaoyue (Frontiers in Earth Science, 2023)
The long-wire with large current source transient electromagnetic (TEM) monitoring with large detection depth, low cost, safety and environmental protection, has unique advantages in the testing and identification of the unconventional reservoir fluid and the evaluation of stimulated reservoir volume. So, the TEM 3D forward modeling become a research hotspot. Although the finite element method (FEM) is a type of numerical algorithm that has been widely applied in three-dimensional (3D) electromagnetic field forward modeling, the efficiency and the accuracy of FEM require further improvement in order to meet the demand of fast 3D inversion. By increasing the order of the basis function and adjusting the principle of the mesh discretization, the precision of the mixed order spectral-element (SEM) result will be increased. The backward Euler scheme is an unconditionally stable technique which can ignore the impact of the scale of the time step. To achieve a better description of the nonlinear electromagnetic (EM) response of the grounded source TEM method and to optimize the efficiency and accuracy/precision of the 3D TEM forward modeling significantly, we proposed the use of 3D TEM forward modeling based on the mixed-order SEM and the backward Euler scheme, which can obtain more accurate EM results with fewer degrees of freedom. To check its accuracy and efficiency, the 1D and 3D layered models are applied to compare the SEM results with the semi-analytical and FEM solutions. In addition, we analyzed the accuracy and efficiency for the SEM method for different order basis functions. Finally, we calculated the long-wire source TEM response for a practical 3D earth model of a shale gas reservoir for fracturing monitoring and tested the feasibility of the TEM method in a hydraulic fracturing monitoring area to further demonstrate the flexibility of the SEM method.